Liquid Metal Alloys in Electronics - Fisher, David J. (Materials Research Foundations Ser., 2020)
Liquid gallium-based alloys are of rapidly increasing interest in electronics because they combine the high electrical conductivity of metals with the ease of manipulation and reconfiguration of liquids. Keywords: Liquid Metals, Gallium-Indium Alloys, Galinstan, EGaIn, Self-Assembled Monolayers, Energy-Harvesting, Reconfigurable Antennae, Sensors, Conformable Electrodes, Stretchable Wires and Interconnects, Self-Healing Circuits, Gallium-Lyophilic Surfaces, Wettability of Liquid Metal, Substrate Topology, Selective Wetting Deposition Technique, Gallium-Indium Droplets on Thin Metal Films, Subs.